HfN Nanoparticles: An Unexplored Catalyst for the Electrocatalytic Oxygen Evolution Reaction. (20th September 2019) - Defilippi, Chiara; Shinde, Dipak V.; Dang, Zhiya; Manna, Liberato; Hardacre, Christopher; Greer, Adam J.; D'Agostino, Carmine; Giordano, Cristina
Abstract: Water electrolysis is one of the most promising methods to produce H2 and O2 as high potential fuels. Comparing the two half‐reactions, the oxygen evolution reaction (OER) is the more difficult to be optimized and still relies on expensive noble metal‐based catalysts such as Ru or Ir. In this paper, we prepared nanoparticles of HfN and Hf2 ON2 and tested them for the OER for the first time. The HfN sample, in particular, showed the highest activity, requiring an overpotential of only 358 mV at 10 mA cm −2 in Fe‐free electrolyte and, above all, exhibiting long‐term stability. This result places this system amongst one of the most promising catalysts for OER tested to date, in terms of sustainability, activity and stability. The prepared nanoparticles are small (less than 15 nm in diameter), well‐defined in shape and crystalline, and were characterised before and after electrochemical testing also via electron microscopy (EM), powder X‐ray diffraction (PXRD) and X‐ray photoelectron spectroscopy (XPS). Abstract : HfN‐Nanopartikel, die über die Harnstoff‐Glas‐Route (UGR) hergestellt wurden, sind hochaktive und stabile Elektrokatalysatoren für die Sauerstoffentwicklungsreaktion (OER). Die Ergebnisse machen diese HfN‐Kern/Schale‐Nanopartikel zu einem der bislang vielversprechendsten Katalysatoren für die OER in Bezug auf Nachhaltigkeit, Aktivität und Stabilität.